Predictive value of unshielded magnetocardiographic mapping to differentiate atrial fibrillation patients from healthy subjects - Guida, Gianluigi; Sorbo, Anna Rita; Fenici, Riccardo; Brisinda, Donatella (Annals of noninvasive electrocardiology, 2018)
Background P‐wave duration, its dispersion and signal‐averaged ECG, are currently used markers of vulnerability to atrial fibrillation (AF). However, since tangential atrial currents are better detectable at the body surface as magnetic than electric signals, we investigated the accuracy of magnetocardiographic mapping (MCG), recorded in unshielded clinical environments, as predictor of AF occurrence. Methods MCG recordings, in sinus rhythm (SR), of 71 AF patients and 75 controls were retrospectively analyzed. Beside electric and magnetic P‐wave and PR interval duration, two MCG P‐wave subintervals, defined P‐dep and P‐rep, were measured, basing on the point of inversion of atrial magnetic field (MF). Eight parameters were calculated from inverse solution with “Effective Magnetic Dipole (EMD) model” and 5 from “MF Extrema” analysis. Discriminant analysis (DA) was used to assess MCG predictive accuracy to differentiate AF patients from controls. Results All but one (P‐rep) intervals were significantly longer in AF patients. At univariate analysis, three EMD parameters differed significantly: in AF patients, the dipole‐angle‐elevation angular speed was lower during P‐dep (p < 0.05) and higher during P‐rep (p < 0.001) intervals. The space‐trajectory during P‐rep and the angle‐dynamics during P‐dep were higher (p < 0.05), whereas ratio‐dynamics P‐dep was lower (p < 0.01), in AF. At DA, with a combination of MCG and clinical parameters, 81.5% accuracy in differentiating AF patients from controls was achieved. At Cox‐regression, the angle‐dynamics P‐dep was an independent predictor of AF recurrences (p = 0.037). Conclusions Quantitative analysis of atrial MF dynamics in SR and the solution of the inverse problem provide new sensitive markers of vulnerability to AF.